Electrically Tunable Reactivity of Substrate‐Supported Cobalt Oxide Nanocrystals. Issue 12 (22nd January 2022) - Sánchez‐Grande, Ana; Nguyën, Huu Chuong; Lauwaet, Koen; Rodríguez‐Fernández, Jonathan; Carrasco, Esther; Cirera, Borja; Sun, Zhaozong; Urgel, José Ignacio; Miranda, Rodolfo; Lauritsen, Jeppe V.; Gallego, José M.; López, Nuria; et al.
Abstract: First‐row transition metal oxides are promising materials for catalyzing the oxygen evolution reaction. Surface sensitive techniques provide a unique perspective allowing the study of the structure, adsorption sites, and reactivity of catalysts at the atomic scale, which furnishes rationalization and improves the design of highly efficient catalytic materials. Here, a scanning probe microscopy study complemented by density functional theory on the structural and electronic properties of CoO nanoislands grown on Au(111) is reported. Two distinct phases are observed: The most extended displays a Moiré pattern (α‐region), while the less abundant is 1Co:1Au coincidental (β‐region). As a result of the surface registry, in the β‐region the oxide adlayer is compressed by 9%, increasing the unoccupied local density of states and enhancing the selective water adsorption at low temperature through a cobalt inversion mechanism. Tip‐induced voltage pulses irreversibly transform α‐ into β‐regions, thus opening avenues to modify the structure and reactivity of transition metal oxides by external stimuli like electric fields. Abstract : CoO monolayers grown on Au are dynamically rearranged under electric fields as shown by scanning tunneling microscopy experiments. Adsorption of active species is only possible on one of the two phases as seen in the images and density functional theory simulations. These results show the importance of dynamic rearrangements under electrochemical conditions particularly to establish robust structure‐activity relationships.